Wakaf CSR : an emperical study of polycentric collaborative waqf governance - Nur Aqidah Suhaili; Mohd Rizal Palil; Rohayati Husin (Penerbit Universiti Kebangsaan Malaysia, 2018)
The key challenge to operate waqf in Malaysia lies within the ability to manage the issue of collaborative governance. In Malaysia, waqf is under the purview of State Islamic Religious Councils (SIRCs) whose permissions are needed to operate waqf legally. However, there are multiple claims that establishing the relationships with SIRCs is complex. Therefore, the main aim of this study is to overcome the paradigm of the complex collaborative relationships between the interested parties of waqf and the SIRCs. For that, the case of Wakaf CSR is chosen as a perfect example of how collaborative waqf relationship is established under polycentric governance. Qualitative approach from case study perspective is utilized for this study apart from secondary data of library search and seminal inputs. The case offers a good insight into how waqf could be operationalized harmoniously into the legal framework using collaborative governance mechanism. The success of the model demonstrated by Wakaf CSR had inspired many versions of collaborative waqf projects with SIRCs. It can be concluded that collaborative governance from polycentric perspective is an ideal formulation for executing the waqf sector in the Malaysian context.